Predictors of emotional burnout in military personnel: a correlational analysis of personal and professional factors - Mykolaichuk, Olena (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2024)
B a c k g r o u n d . The relevance of studying emotional burnout in military personnel is driven by the extreme circumstances of today, considering the specific nature of military-professional activities, the influence of aggravating factors, and the growing need for effective preventive and corrective measures to support the mental health of military personnel. The purpose of the study is to examine the personal and professional factors, in the context of motivational theory, which can be predictors of this phenomenon.M e t h o d s . The study employed both theoretical methods (analysis, comparison, generalization, systematization) and empirical methods, namely: the Burnout Assessment Tool (BAT), the Basic Psychological Need Satisfaction and Frustration Scale (BPNSFS), the Interpersonal Guilt Rating Scale – 15s (IGRS-15s), methods of mathematical statistics.R e s u l t s . The prevalence of burnout among military personnel was analyzed, along with the factor loadings of components contributing to the development of the phenomenon as a whole. A close relationship was found between the facets of motivational theory (autonomy, relatedness, competence, guilt) and emotional burnout.C o n c l u s i o n s . The study identified the characteristics of emotional burnout among the Armed Forces of Ukraine personnel. Personal predictors of this phenomenon were analyzed through the motivational theory with a focus on basic need satisfaction. Frustration, guilt and selfdemandingness occupy a special place among the factors contributing to this phenomenon. The importance of implementing preventive and psychocorrectional programs in military units, involving all categories of military personnel regardless of age, duration of service, or professional affiliation, is emphasized.
Keywords: burnout, guilt, motivation, autonomy, relatedness, frustration, military personnel